Development of high-power, long-pulse, multi-frequency ECH/CD system for JT-60SA. (5th January 2022) - Kobayashi, T.; Yamazaki, H.; Hiranai, S.; Sawahata, M.; Terakado, M.; Ishita, K.; Hinata, J.; Sato, F.; Wada, K.; Toida, N.; Ikeda, R.; Shinya, T.; et al.
Abstract: A gyrotron and a matching optics unit (MOU) for the multi-frequency electron cyclotron heating and current drive (ECH/CD) system in JT-60SA have been developed successfully. The gyrotron demonstrated stable operation at high powers of 1.5 MW for 5 s and 1.9 MW for 1 s at 110 GHz. To obtain high HE11 mode purity (>90%) at the outlet of the waveguide in the ECH/CD launcher, a MOU for operating at three frequencies of 82 GHz, 110 GHz, and 138 GHz that includes three pairs of water-cooled phase correcting mirrors has been developed, which allows the mirrors to be changed without opening the evacuated MOU. The mode purity at the inlet of a dummy load in the transmission line was evaluated at high-power and an HE11 mode purity of >90% was obtained at three frequencies.